GENDER VIOLENCE AND FEMALE DEHUMANIZATION IN WHITE CHRYSANTHEMUM (2018), BY MARY LYNN BRACHT - Alves, Elis Regina Fernandes [UNESP]; Santos, Danielle Fabricio dos; Rocha, Sara Almieira da (Univ Estado Mato Grosso, 2024)
This article aims to analyze the work White Chrysanthemum , by Mary Lynn Bracht, focusing on the female character Hana and her condition as a comfort woman . When dealing with gender roles, violence and the condition of Korean women, authors such as Beauvoir (2019a, 2019b), Okamoto (2013), among others, were used. Then, Showalter (2014) was used to relate the work to certain phases of female writing. The research also analyzed the symbolism of the sea in the work, based on Chevalier (2001). Finally, it was verified there was the dehumanization of characters that resemble the figure of the prostitute within literary molds.
Keywords: comfort women; gender violence; White Chrysanthemum